Ex-vivo Ex-Vivo Absorption Study of a Novel Dabigatran Etexilate Loaded Nanostructured Lipid Carrier Using Non-Everted Intestinal Sac Model - Abed, haithem N; A. Hussein, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2019)
Abstract The purpose of our study was to develop Dabigatran Etexilate loaded nanostructured lipid carriers (DE-NLCs) using Glyceryl monostearate and Oleic acid as lipid matrix, and to estimate the potential of the developed delivery system to improve oral absorption of low bioavailability drug, different Oleic acid ratios effect on particle size, zeta potential, entrapment efficiency and loading capacity were studied, the optimized DE-NLCs shows a particle size within the nanorange, the zeta potential (ZP) was 33.81±0.73mV with drug entrapment efficiency (EE%) of 92.42±2.31% and a loading capacity (DL%) of 7.69±0.17%. about 92% of drug was released in 24hr in a controlled manner, the ex-vivo intestinal permeation study using the non-everted sac model shows four folds increment in the permeation of DE-NLCs compared to dabigatran etexilate suspension (DE-S).